Regional gray matter volume mediates the relationship between neuroticism and depressed emotion - Yang, Junyi; Huangfu, Xiaoyang; Tong, Dandan; He, Anming (Frontiers in Psychology, 2022)
The underlying psychological mechanism of the effect of neuroticism on depressed emotion has been widely studied. However, the neural mechanism of this relationship remains unclear. Therefore, the present study aimed to apply voxel-based morphometry (VBM) to explore the neural mechanism of the relationship between depressed emotion and neuroticism in healthy and young participants through longitudinal tracking research. The behavioral results showed that neuroticism was positively related to depressed emotion at T1 and T2 (6 months later). The VBM analysis revealed that neuroticism positively associated with the gray matter volume (GMV) in the dorsal medial prefrontal cortex (dmPFC). Mediation analysis was conducted to investigate the neural basis of the association between depressed emotion and neuroticism. The mediation result revealed that GMV of the dmPFC partially mediates the relationship between neuroticism and depressed emotion at T1 but not T2. Together, these findings suggest that the gray matter volume of dmPFC could may affect the relationship between depressed emotion and neuroticism.